2020
DOI: 10.1111/jfir.12216
|View full text |Cite
|
Sign up to set email alerts
|

Activity Strategies, Agency Problems, and Bank Risk

Abstract: We investigate whether diversification affects bank risk taking in the U.S. banking industry, and whether this relation is partially explained by agency theory. Our results show that U.S. banks with a relatively high share of noninterest income become riskier when moving toward non‐interest‐income‐generating activities, especially activities from investment banking, proprietary trading, and so on. Diversification not only affects conditional average risk, but also the dispersion of risk. Moreover, diversified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 86 publications
1
3
0
Order By: Relevance
“…SIZE has a positive and significant effect on 5 percent of bank stability. This finding is in line with the research conducted by Abuzayed et al (2018); Ayadi, Ayadi, and Trabelsi (2019); Tran, Hassan, Girerd-Potin, and Louvet (2020), which argued that an increase in the size of the bank would increase the stability of the bank as an effect of increasing the banking system to be more effective and efficient.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…SIZE has a positive and significant effect on 5 percent of bank stability. This finding is in line with the research conducted by Abuzayed et al (2018); Ayadi, Ayadi, and Trabelsi (2019); Tran, Hassan, Girerd-Potin, and Louvet (2020), which argued that an increase in the size of the bank would increase the stability of the bank as an effect of increasing the banking system to be more effective and efficient.…”
Section: Discussionsupporting
confidence: 89%
“…However, in the banking sector, diversification effects can cause agency problems as a result of the emergence of diversification costs (Wu et al, 2020). In various previous studies, many researchers found that the implementation of the income diversification strategy in banking resulted in a decrease in the stability (Abuzayed et al, 2018;Lee et al, 2020;Tran et al, 2020) as a result of the bank's inability to mitigate risk. Cost inefficiency and disruption become the bank's main focus as a financial intermediary institution, so they affect the bank's overall performance.…”
Section: Conclusion Limitations and Suggestionsmentioning
confidence: 99%
“…The bank's maximization problem is to optimize the choice variables L , r l , i and r d in Equation (3) in order to maximize Π in each time period, given an RRF‐computed ∑ ( D ). The profit function above is a simplification of the profit‐generating activities (beyond traditional intermediation) of banks, which in the recent years include many non‐interest activities (Tran et al, 2020). However, this simplification is necessary to allow the model to focus on how different lending practices affect bank stability.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we used the Z-score as a proxy for bank stability; this measure has been widely used in various previous studies, for example, Abdelbadie and Salama (2019), Tran et al (2020); Marie et al (2021), etc. The Z-score was first proposed by Professor Edward I. Altman of the Leonard N. Stern School of Business of New York University to study various enterprises in the US.…”
Section: Variablesmentioning
confidence: 99%